HISTORICAL STUDY OF THE KASHKADARYA OASIS: STAGES, RESULTS AND PROSPECTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article considers the Kashkadarya oasis to be one of the ancient cultural and historical regions of Central Asia. This article analyzes the stages of historical study of the oasis, the results of archaeological excavations, information from written sources, and modern scientific research. It also covers important stages in the process of historical study and the factors that influenced them on a chronological basis. The article reviews the process of scientific research of the Kashkadarya oasis and indicates future directions in this regard.